2011
DOI: 10.1016/j.trb.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The value of travel time variance

Abstract: This paper considers the value of travel time variability under scheduling preferences that are de…ned in terms of linearly time-varying utility rates associated with being at the origin and at the destination. The main result is a simple expression for the value of travel time variability that does not depend on the shape of the travel time distribution. The related measure of travel time variability is the variance of travel time. These conclusions apply equally to travellers who can freely choose departure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(99 citation statements)
references
References 14 publications
1
94
0
Order By: Relevance
“…The use of this model to value travel time variability is due to Fosgerau and Engelson (2011) who used linear utility rates to find a cost measure that is linear in the mean and variance of the travel time distribution when ℎ is constant. In this case, the cost measure is additive over independent travel time components, and the additivity property was characterized in Engelson and Fosgerau (2011).…”
Section: Bibliographical Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of this model to value travel time variability is due to Fosgerau and Engelson (2011) who used linear utility rates to find a cost measure that is linear in the mean and variance of the travel time distribution when ℎ is constant. In this case, the cost measure is additive over independent travel time components, and the additivity property was characterized in Engelson and Fosgerau (2011).…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…The corresponding absolute measure could be defined as the planning time, which would be the buffer time, since the mean travel time enters the cost measure separately. Fosgerau and Engelson (2011) showed that a scheduling model with constant ℎ and affine leads to a mean-variance cost measure, where the coefficients 1 and 2 do not depend on the travel time distribution. Then the utility rates considered by Fosgerau and Engelson (2011) lead to a mean-dispersion measure of the kind considered in this paper.…”
Section: Type 3: Mean-dispersion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value commuters attach to a marginal reduction in travel time variability is referred to as the value of (travel time) reliability and can be inferred from observed scheduling choices (Fosgerau and Karlström, 2010;Fosgerau and Engelson, 2011). Typically, the value of reliability is derived using the presumption that commuters have rational expectations and an infinite memory.…”
Section: Introductionmentioning
confidence: 99%
“…Fosgerau and Karlström (2010) presented a model that estimates the value of travel time variability based on scheduling preferences. Fosgerau and Engelson (2011) considered the value of travel time variability under scheduling preferences that were defined in terms of linearly time-varying utility rates associated with being at the origin and at the destination. They have shown that a measure related to travel time variability is variance of travel time.…”
Section: Introductionmentioning
confidence: 99%